Comparison of the Thermo-Hydraulic Response of MELCOR 1.8.6 and 2.1 for SBO Accident for APR 1400 Reactor - Ghaderinia, F.; Rahgoshay, M.; Jafari, J.; Dauria, F. S. (Atom Indonesia, 2024)
An analysis of thermohydraulic response during a station blackout (SBO) accident for the APR 1400 nuclear power plant is performed using MELCOR version 1.8.6. MELCOR 1.8.6 results for the SBO scenario are benchmarked with MELCOR 2.1. The simulation of the SBO accident with MELCOR 2.1 was done by the APR 1400 reactor designer company (KEPCO). This research consists of two parts; the first part is related to the results of MELCOR 1.8.6, and the thermo-hydraulic analysis of MELCOR1.8.6 has been done. Analysis of thermohydraulic response is focused on investigating thermohydraulic parameters, such as core pressure, fuel clad temperature, water mass flow rate in the core, time of fuel clad failure, time of lower head failure, and time of containment failure. In the second part, the results of MELCOR version 1.86 have been benchmarked with the results of MELCOR 2.1. The results of the analysis of containment pressure changes in version 1.8.6 showed that the effect of pressure increase in containment is mostly due to the increase in carbon dioxide mass, but in version 2.1, the increase in pressure is more due to water vapor.